Human papillomavirus vaccination in Africa: An airway perspective. (February 2023) - McGuire, J.K.; Kabagenyi, F.; Peer, S.
Abstract: Introduction: Recurrent respiratory papillomatosis (RRP) is a chronic condition caused by Human papillomavirus six (HPV-6) and HPV-11 that involves the respiratory tract. Disease severity ranges from mild (hoarseness), through to severe (stridor, respiratory distress and airway emergencies). Africa has the fastest growing and youngest population of all the continents. It also has the greatest burden of cervical cancer. There is an association with infection of the oncogenic HPV strains and the strains responsible for RRP. It is reasonable to conclude that although RRP may be underestimated in low-to-middle-income countries, it poses a considerable health risk to Africa. The primary aim of this project was to assess the suitability of HPV vaccination coverage on the African continent. Methods: A prospective study was designed to consist of an online survey. It was distributed to 135 African otolaryngologists. Questions focussed on HPV vaccination programmes; whether they were government directed; and their rollout. Information from countries that had multiple otolaryngologists respond to the survey were compared. Additionally, data review and corroboration were performed. Results: There were 58 (43%) participants from 19 countries. Nine countries reported a national vaccination programme (NVP), five used Cervarix; four used quadrivalent Gardasil. Collateral data revealed 18 of 54 countries had NVP in Africa and 26 countries had completed HPV vaccine pilot or demonstration projects. Conclusions: HPV vaccination in Africa should be urgently re-evaluated to include the HPV-6 and HPV-11 strains that cause JORRP, which have not been recognised during national vaccination programme planning.